Patrera cita - Oliveira, Luiz Fernando M.; Brescovit, Antonio D. (Zenodo, 2021)
Patrera cita (Keyserling, 1891) Figs 8A–G; 9A–E; 10A–F; 27A Anyphaena cita Keyserling, 1891: 94, figs 55–55a (Syntypes three male and one female from Paineiras, Corcovado (currently Parque Nacional da Tijuca, 22°57’43.2”S 43°14’52.8”W), Prof. Göldi leg., deposited in BMNH 1890.4.1.603-606, examined). Lectotype male BMNH 1890.4.1.603 and paralectotypes BMNH 1890.4.1.604-606 here designated. Wulfila cita : Simon, 1897: 94, fig 94. Teudis citus : Petrunkevitch, 1911: 516. Patrera cita : Brescovit, 1997: 33. Other material examined. BRAZIL. Bahia : Una, Reserva Biológica do Una (15°10’23”S; 39°7’56”W), 1♂, 15– 28.XI.2000, A.D. Brescovit et al. leg. (IBSP 47889); Minas Gerais : Casa Grande (20º47’34”S; 43º55’49”W), 1♂, 02.XI.1995, A. Gorgonio leg. (IBSP 6011); Espírito Santo : Santa Teresa, Estação Biológica de Santa Lúcia (19°57’10”S; 40°31’30”W), 1♀, 28.VII.2006, T. Souza et al. leg. (IBSP 121213); Reserva Biológica Augusto Ruschi (19°54’20”S; 40°33’44”W), 1♂, 1♀, IV–VIII.2006, T. Souza, T. Bernabé & E. Soeiro leg. (IBSP 121657); Ca- riacica, Alto do Alegre, Reserva Biológica de Duas Bocas, 596m (20°16’24”S; 40°30’31”W), 1♂, 2♀, 13.X.2005, T. Souza leg. (IBSP 134813); Rio de Janeiro : Cachoeiras de Macacu (22°27’46”S; 42°39’10”W), Estrada do Imperador, 1♀, 02.VIII.1996, R.S. Bérnils & P.H. Labiak leg. (MZSP 15149); 7♂, 1♀ (IBSP 138981; IBSP 138985; IBSP 138986; IBSP 138995; IBSP 138996; IBSP 138999; IBSP 139001), all collected in 08–12.X.2001 by Equipe Biota; Guapimirim, Estação Ecológica Estrada do Paraíso (22°29’4”S; 42°53’7”W), 1♂, 4♀, 1imm. (MZSP 14999; MZSP 15002; MZSP 15004; MZSP 15005); all collected in 04–07.VII.1996 by R.S. Bérnils; Magé (22°39’10”S; 43°2’27”W), 1♂, 14.XII.1986, R.L.C. Baptista & N.D. Santos leg. (MNRJ 3186); Vila Inhomirim (22°34’17.93”S; 43°11’5.74”W), Fazenda Mandioca, 550m alt., 13–14.X.1996, 2♂, 1♀, 1imm, R.S. Bérnils leg. (MZSP 15707); Petrópolis, Fazenda Ranchinho da Roça (22°30’18”S; 43°10’44”W), 2♂, 3♀ (IBSP 139442; IBSP 139448; IBSP 139450; IBSP 139453), all collected in 12–14.XI.1999 by Equipe Biota; 1♂, 2♀ (IBSP 139928; IBSP 139932; IBSP 139942), all collected in 08–15.II.2000 by Equipe Biota; Teresópolis (22°24’43”S; 42°57’57”W), 900–1000m, 1♀, III.1946, H. Sick leg. (AMNH); Parque Nacional da Serra dos Órgãos (22°29’35”S; 43°4’24”W), 2♂, 5♀ (IBSP 139521; IBSP 139527; IBSP 139540; IBSP 139556; IBSP 139557), all collected in 18–22.VIII.2001 by Equipe Biota; 1♂, 2♀, 10–22.XI.2010, R.P. Indicatti; F.U. Yamamoto & J.P.P. Barbosa leg. (IBSP 214454); 1♀, 18– 31.XII.2011, R.P. Indicatti & B. Gambaré leg. (IBSP 219403); 1♀, VIII.1987, N.D. Santos leg. (MNRJ 3187); Rio de Janeiro, Tijuca (22°55’27.66”S; 43°13’56”W), 1♀, 07.XI.1989, A.B. Kury leg. (IBSP 212909); Represa do Rio Grande, Serra de Bangu (22°54’20”S; 43°28’14”W), 6♂, 4♀, I.1967, M. Alvarenga leg. (MZSP 14107; MZSP 14155); Angra dos Reis (23°0’36”S; 44°19’6”W), Ilha Grande, Ponta da Aripeba, 3♀, 13–16.XI.1993, A.B. Bon- aldo leg. (IBSP 212656); São Paulo : Iporanga (24°35’09”S; 48°35’34”W), Quilombo de Bombas, 2♂, 3♀, 4.VI.1994, R. Pinto da Rocha leg. (MZSP ex. 14302); Parque Estadual de Intervales (24°16’6.3”S; 48°24’49.7”W), 1♂, 22.V.2004, B. Buzatto leg. (IBSP 43929); Parque Estadual Turístico do Alto do Ribeira (PETAR) (24°28’30”S; 48°39’30”W), 44♂, 22♀ (IBSP 139312; IBSP 139315–IBSP 139319; IBSP 139321; IBSP 139323; IBSP 139324; IBSP 139326; IBSP 139327–IBSP 139347; IBSP 139351–IBSP 139353; IBSP 139355–IBSP 139360; IBSP 139362– IBSP 139367), all collected in 12–18.X.2001 by Equipe Biota; Capão Bonito, Parque Estadual de Intervales (24°16’6.3”S; 48°24’49.7”W), 1♂, 08–10.X.2011, A.D. Brescovit et al. leg. (IBSP 168648); Ribeirão Grande, Parque Estadual de Intervales (24°16’6.3”S; 48°24’49.7”W), 1♂, IX.2004, B. Buzatto leg. (IBSP 56948); Jundiaí, Reserva Biológica Municipal da Serra do Japi (23°14’00”S; 46°58’00”W), 1♂, 04.II.1998, A.J. Santos leg. (IBSP 37566); 1♀, 2004, A.D. Brescovit, D. Polotow & T.H. Kawamoto leg. (IBSP 68687); 2imm., 2004, Alunos Curso Pós USP leg. (IBSP 138864); Tapiraí (23º57’49”S; 47º30’ 26”W), 6♂, 2♀, 3imm. (IBSP 13055; IBSP 13120; IBSP 13163; IBSP 13171; IBSP 13236; IBSP 13253; IBSP 13283), all collected in 11–13.IX.1997 by C. Rheims & V.C. Onófrio; Santo André (23°39’50”S; 46°32’16”W), Vila de Paranapiacaba, 1♂, 14–23.VI.2010, R.S. Gonzáles leg. (IBSP 169958); Reserva Biológica do Alto da Serra de Paranapiacaba (23º46’18”S; 46º20’24”W), 3♂, 2♀, 1imm., 27.VII.1999, C.A. Rheims leg. (IBSP 23882); 1♂, 27.VII.1999, F.S. Cunha leg. (IBSP 23966); 6♂, 1♀, 14– 16.XII.2003, C.A. Rheims & R.P. Indicatti leg. (IBSP 52092); 1♂, 4♀ (IBSP 226782; IBSP 226786; IBSP 226795; IBSP 226797; IBSP 226798), all collected in 03.III–22.II.2012 by Z. R. Mendes; 2♂, 27–28.X.2007, Equipe Butan- tan leg. (IBSP 88550; IBSP 88564); 3♂, 04–05.VIII.2010, A.P.S. Silva leg. (IBSP 169384); 1♂, 17.V.1998, R. Pinto da Rocha, C. Firmo & R. Cordenonsi leg. (MZSP 16394); Mogi das Cruzes, Parque Natural Municipal da Serra do Itapety (23°29’07”S; 46°12’21”W), 1♂, 13–19.X.2003, Equipe Biota leg. (IBSP 139519); São Bernardo do Campo (23°41’38”S; 46°33’54”W), 1♂, 07.II.1968, P. de Biasi, Tanni & Boschero leg. (MZSP 12138); Parque Estoril (-23.7698; -46.5171), 1♂, 11–16.VIII.2006, B. Távora leg. (IBSP 72176); Embu-Guaçu (23°49’51”S; 46°48’44”W), Cabeceiras do Rio Embu-Guaçu, Campos da Serra, 1♀, 03.IV.1943, F. Lane leg. (MZSP 14112); Salesópolis, Estação Biológica de Boracéia (23º38’00”S; 45º52’00”W), 5♂, 08–10.IV.2000, A.D. Brescovit et al. leg. (IBSP 27133); (23°37’53”S; 45°52’13”W), 3♂, VII.2005, A.D. Brescovit et al. leg. (IBSP 55290); 2♂, 17. III.2007, F.V. Yamamoto leg. (IBSP 79064; IBSP 79065); 1♂, 1♀, 03.III.1992, R.L.C. Baptista leg. (IBSP 212905); 78♂, 21♀ (IBSP 138443; IBSP 138444; IBSP 138447–IBSP 138449; IBSP 138794–IBSP 138804; IBSP 138806; IBSP 138808–IBSP 138813; IBSP 139368–IBSP 139370; IBSP 139372–IBSP 139381; IBSP 139383; IBSP 139384; IBSP 139386–IBSP 139396; IBSP 139398–IBSP 139400); all collected in 18–24.V.2001 by Equipe Biota; 1♂, 26.V.2006, M. Uehara Prado leg. (IBSP 143243); 1♀, 01–02.IX.1965 (MZSP 4760); 1♀, 23.IX.1965 (MZSP 4855); 2♂, 28.II.1967 (MZSP 6118); 1♂, 1♀, 20.X.1965 (MZSP 12160); 1♀, 27.II.1967 (MZSP 6085), all collected by P. de Biasi; 1♀, 18.VIII.1966, Expedition of MZSP (MZSP 5922); 1♂, 1♀, 01.II.1961 (MZSP 9774); 1♀, 12.V.1961 (MZSP 12208); 1♂, 10.XI.1960 (MZSP 12245), all collected by K. Lenko; 2♂, 1♀, 29.XI.1951 (MZSP 12196); 1♀, 13–19.III.1950 (MZSP 12214); 1♀, 06–09.VII.1948 (MZSP 12266), all collected by H.F. de A. Camargo; Ribeirão Grande (24°5’56”S; 48°21’54”W), 1♀, 08.IV.2006, G. Machado leg. (IBSP 79313); Cotia (23°36’14”S; 46°55’08”), Caucaia do Alto, 19♂, 4♀ (IBSP 139823; IBSP 139824; IBSP 139826; IBSP 139828; IBSP 139829; IBSP 139831; IBSP 139832; IBSP 139836; IBSP 139838; IBSP 139841; IBSP 139844; IBSP 139846; IBSP 139847; IBSP 139849; IBSP 139851; IBSP 139854; IBSP 139855–IBSP 139858; IBSP 139860); all collected in 18–28.VI.2002 by Equipe Biota; Reserva Florestal do Morro Grande (23°38’58.12”S; 46°57’45.99”W), 21♂, 5♀ (IBSP 37162; IBSP 98144; IBSP 98146; IBSP 98149; IBSP 98152–IBSP 98154; IBSP 98156–IBSP 98159; IBSP 98161–IBSP 98169; IBSP 98172; IBSP 98173); all collected in 13–30.VI.2002 by Equipe Biota; São Paulo, São Paulo, Parque Estadual do Jaraguá (23°27’34.3”S; 46°46’2.8”W), 1♂, 14–19.X.2002, Equipe Biota leg. (IBSP 139622); Campus Instituto Butantan (23º33’00”S; 46º43’00”W), 1♂, 18.X.2007, Alunos Curso USP 2007 leg. (IBSP 87951); Parque do Estado (23°38’24.6”S; 46°37’3.1”W), 1♂, 13.I.1960, F. Lane leg. (MZSP 3876); Parque Água Branca, Barra Funda (23°34’00”S; 46°43’0”W), 1♂, 07.XII.1951, H.F. de A. Camargo leg. (MZSP 14114); Parque Estadual da Serra da Cantareira, Núcleo Pedra Grande (23°24’5”S; 46°35’24”W), 2♂, 1♀, 15.XII.2002, R. Pinto da Rocha et al. leg. (IBSP 210222); Engenheiro Marsilac (- 23.9078S; - 46.7069W), 1♂, 06.X.1965, P. de Biasi leg. (MZSP 4601); 2♀, 12.III.1967, P. de Biasi & J.L.M. Leme leg. (MZSP 6049; MZSP 14152); Parelheiros, Colônia (23°52’15”S; 46°42’30”W), 1♀, 12.III.1967, P. de Biasi & J.L.M. Leme leg. (MZSP 6099); Parque Estadual da Serra do Mar, Núcleo Curucutu (23º58’13”S; 46º43’37”W), 1♂, 29.VIII.2009, R.P. Indicatti leg. (IBSP 149733); Santo André, Estação Biológica de Paranapiacaba (antigo Alto da Serra) (23°46’44”S; 46°18’38”W), 1♂, 29.X.1990, R.L.C. Baptista & A.P.C. Baptista leg. (MZSP 12009); 3♂, 2♀, 18–27.X.1952, W.C.A. Bokermann leg. (MZSP 12205; MZSP 12209; MZSP 12322); 1♂, 17.V.1998, R. Pinto da Rocha, C. Firmo & R. Cordenonsi leg. (MZSP 16422); Biritiba Mirim, Barragem do Rio Biritiba (23°36’12.143”S; 46°5’13.654”W), 1♂, 1♀, 16.VII.2004, Equipe IBSP leg. (IBSP 117523); Ubatuba (23°26’2”S; 45°4’15”W), Reserva de Joatinga, Praia do Sono, 1♂, 07–17.VI.2002, I. Cizauskas & A. G. Sugimoto leg. (IBSP 43419); Taquaral, Fazenda Angelim (23°26’50”S; 45°04’00”W), 3♂, 1♀, 05.VII.1997, C.A. Rheims leg. (IBSP 13841; IBSP 13849); 30♂, 1♀, 17–19.XII.2003, C.A. Rheims & R.P. Indi- catti leg. (IBSP 52276 IBSP; 215412–IBSP 215418; IBSP 215420–IBSP 215425; IBSP 215428–IBSP 215438; IBSP 215440–IBSP 215443), all collected in 15.II.2012 by A.D. Brescovit et al. Parque Nacional da Serra do Mar, Praia de Picinguaba (23°19’31”S; 44°49’55”W), 1♂, 07–10.VII.2001, D.M. Takiya leg. (IBSP 36048); Parque Estadual da Ilha Anchieta (23º32’00”S; 45º03’00”W), 1♀, 23–30/VII/2001, Equipe Biota leg. (IBSP 56403); Parque Estad- ual Ilha Anchieta (23º32’00”S; 45º03’00”W), 16♂, 20♀ (IBSP 138599; IBSP 138602; IBSP 138604; IBSP 138606; IBSP 138608–IBSP 138612; IBSP 138614; IBSP 138615; IBSP 138617; IBSP 138620; IBSP 138624; IBSP 138626– IBSP 138630; IBSP 138632; IBSP 138635; IBSP 138636; IBSP 138638–IBSP 138641; IBSP 138643; IBSP 138644; IBSP 138648; IBSP 138649; IBSP 138651; IBSP 214178), all collected in 23–30.VII.2001 by Equipe Biota; Itanhaém (24°10’58”S; 46°47’20”W), restinga, 4♂, X.1999, H.F. Japyassú leg. (IBSP 27734); Estrada de Itanhaém, 1♂, 28.IX.1961, P. de Biasi leg. (MZSP 14113); Estação Ecológica São Camilo, Suarão (24°10’60”S; 46°46’60”W), 1♂, 1♀, XII.2010, G. Aparecida & M. Pessoa leg. (IBSP 224503; IBSP 224504); Ilha da Queimada Grande (24°29’8.5”S; 46°40’31.22”W), 2♂, 04–05.XII.1995, A.D. Brescovit & R. Bertani leg. (IBSP 7867); 2♂, 3♀, 23–24.I.1997, A.D. Brescovit & R. Bertani leg. (IBSP 7914); 1♂, 13–16.X.2000, R. Bertani leg. (IBSP 27687); São Vicente, Horto Florestal de São Vicente (currently Parque Ecológico Voturuá) (23º57’34.71”S; 46º21’50.48”W), 6♂, XII.2005 – II.2006, F.J. Zara leg. (IBSP 149747); Caraguatatuba (23°37’12”S; 45°24’46”W), 1♂, 10–16.VII.1965, Expedition of MZSP leg. (MZSP 4942); 1♂, 1♀, 16–17.II.1942, B.M.A. Soares leg. (MZSP 10193); Santos (23°56’13.16”S; 46°19’30.34”W), 3♂, 01–05.X.2007, E.O. Machado leg. (IBSP 118409); Vale do Rio Jurubatuba (23°51’50”S; 46°17’51”W), 33♂, 23♀ (IBSP 119482; IBSP 119483; IBSP 119485–IBSP 119505; IBSP 119507–IBSP 119522), all collected between III.2007 – XII.2007 by A.A. Nogueira et al. São Sebastião, Praia Toque Toque Pequeno (23°49’8”S; 45°32’6”W), 1♂, 20–23.XI.2008, G.P. Perroni leg. (IBSP 119745); Barra do Una (24º27’30”S; 47º04’45”W), 3♂, 5♀ (MZSP 9728; MZSP 12176; MZSP 12197; MZSP 12206; MZSP 12213), all collected in 03.VI.1961 by K. Lenko; Cubatão (23°53’42”S; 46°25’30”W), 1♂, 07.IX.1941, B.A.M. Soares leg. (MZSP 14153); Mata de Encosta da Copebrás (23º50’06”S; 46º23’52”W), 40♂, 18♀ (IBSP 137756–IBSP 137763; IBSP 137766– IBSP 137777; IBSP 137779–IBSP 137788), all collected between VI–XII.2008 by A.A. Nogueira et al. Ilhabela, Parque Estadual de Ilhabela (23°51’7”S; 45°20’38”W), 13♂, 10♀ (IBSP 138522; IBSP 138524–IBSP 138529; IBSP 138531–IBSP 138533; IBSP 138536–IBSP138540; IBSP 138543–IBSP 138549), all collected in 09–15.X.2001 by Equipe Biota leg.; Ilha de São Sebastião (23°48’54”S; 45°22’14”W), 2♂, 16–19.I.1950 (MZSP 12183); 1♂, 02.II.1950 (MZSP 12210); 10♂, 4♀, 26–29.I.1951 (MZSP 12264); 1♀, 20.III.1948 (MZSP 12265); all collected by H. Urban; São Miguel Arcanjo, Parque Estadual Carlos Botelho (24º07’53”S; 47º56’57”W), 2♂, 3♀, 12–16.X.1990, A.B. Bonaldo leg. (IBSP 221067); Miracatu, Fazenda Itereí (24º03’00”S; 47º13’00”W), 50♂, 13♀ (IBSP 139762 IBSP 139764–IBSP 139796; IBSP 139802–IBSP 139804; IBSP 139806–IBSP 139809; IBSP 139811–IBSP 139813; IBSP 139816–IBSP; 139820; IBSP 139822); all collected in 20–26.IX.2001 by Equipe Biota; Peruíbe, Estação Ecológica Juréia-Itatins (24º33’015”S; 47º13’292”W), 1♂, 02.XI.1995, R. Bertani & O. Marques leg. (IBSP 6358); 22♂, 21♀, 1imm., 21.III.1997, A.D. Brescovit et al. leg. (IBSP 9584; IBSP 9719; IBSP 9776; IBSP 9784; IBSP 9802; IBSP 9862; IBSP 9877; IBSP 9895; IBS P 9946); 11♂, 7♀, 2imm., 30.IX.1997 – 02.X.1997, R. Bertani et al. leg. (IBSP 13449; IBSP 13463; IBSP 13523; IBSP 13526; IBSP 13622; IBSP 13638; IBSP 13665); 36♂, 14♀, 18imm., 15–17.XII.1998, A.D. Brescovit et al. leg. (IBSP 22192; IBSP 22208; IBSP 22236; IBSP 22240; IBSP 22260; IBSP 22276; IBSP 22299; IBSP 22336; IBSP 22345; IBSP 22366; IBSP 22397; IBSP 22471; IBSP 22515; IBSP 22516; IBSP 22545; IBSP 22580; IBSP 22611; IBSP 22619; IBSP 22637; IBSP 22651; IBSP 22679; IBSP 22699; IBSP 22706; IBSP 22740; IBSP 22748; IBSP 22795; IBSP 22824; IBSP 22855; IBSP 22860; IBSP 22886; IBSP 22905; IBSP 22925; IBSP 22968; IBSP 22985; IBSP 23006; IBSP 23012); 35♂, 18♀, 15imm., 03.V.1999, A.D. Brescovit et al. leg. (IBSP 24569; IBSP 24596; IBSP 24619; IBSP 24628; IBSP 24640; IBSP 24678; IBSP 24695; IBSP 24700; IBSP 24741; IBSP 24782; IBSP 24790; IBSP 24804; IBSP 24881; IBSP 24942; IBSP 24956; IBSP 24975; IBSP 24986; IBSP 25006; IBSP 25022; IBSP 25042; IBSP 25122; IBSP 25138; IBSP 25146; IBSP 25205; IBSP 25237; IBSP 25261; IBSP 25267; IBSP 25320; IBSP 25346; IBSP 25353; IBSP 25441; IBSP 25479; IBSP 25488; IBSP 25494; IBSP 25517; IBSP 25521; IBSP 25561; IBSP 25813; IBSP 25822); Morro do Guaraú (24°28’59”S; 47°10’39”W), 1♂, 28.II.1996, R.S. Bérnils leg. (MZSP 14987); Pariquera-Açu, Vale do Ribeira, cam- pus do Instituto Agronômico de Campinas (24°42’36”S; 47°52’48”W), 1♂, [without date], I. Rinaldi leg. (MZSP 60331); 1♂ [without date], E. Wienskoski leg. (MZSP 60390); 1♀, 01.II.2000, I. Rinaldi & L.C. Forti leg. (MZSP 62930); Iguape (24°42’38”S; 47°33’14”W), 5♂, 1♀, 01–05.XI.1968, P. de Biasi & J.L.M. Leme leg. (MZSP 14154); Cananéia (25°0’54”S; 47°55’37”W), 1♂ [without date], E. Wienskoski leg. (MZSP 60389); Paraná : Adrianópolis, Vale do Ribeira (24º43’83”S; 48º41’71”W), 1♀, 15.VI.2004, D.M. Battesti & M. Arzua leg. (IBSP 44040); Anto- nina (25º25’44”S; 48º42’43”W), 32♂, 2♀ (IBSP 221073; IBSP 221079; IBSP 221081; IBSP 221082; IBSP 221084), all collected in 04.VIII–29.XII.1986 by Equipe Profaupar col.; Reserva Natural do Rio Cachoeira (25°19’15”S; 48°42’24”W), 36♂, 22♀ (IBSP 98595; IBSP 98599; IBSP 98601; IBSP 98604; IBSP 98607; IBSP 121666; IBSP 131173), all collected between 20.VI.2003 – 19.IV.2004 by H. Höfer et al. 5♂, 1♀ (IBSP 151050; IBSP 151053; IBSP 151054), all collected in 24–27.IX.2005 by E.E. S. Álvares; 2♂, 4♀ (IBSP 151055–IBSP 151058; IBSP 151101–IBSP 151102), all collected in 24–26.IX.2005 by H. Höfer; 5♂, 3♀ (IBSP 151060; IBSP 151062; IBSP 151104; IBSP 151105; IBSP 151107; IBSP 151110), all collecte : Published as part of Oliveira, Luiz Fernando M. & Brescovit, Antonio D., 2021, The spider genus Patrera Simon (Araneae: Dionycha, Anyphaeninae) in the Atlantic Forest biome, with the description of one new species from Brazil, pp. 201-246 in Zootaxa 4991 (2) on pages 217-222, DOI: 10.11646/zootaxa.4991.2.1, http://zenodo.org/record/5028185 : {"references": ["Keyserling, E. (1891) Die Spinnen Amerikas. Brasilianische Spinnen. Vol. 3. Bauer & Raspe, Nurnberg, 278 pp.", "Simon, E. (1897) Histoire naturelle des araignees. Tome Second. Deuxieme Edition. Roret, Paris, 192 pp. https: // doi. org / 10.5962 / bhl. title. 51973", "Petrunkevitch, A. (1911) A synonymic index-catalogue of spiders of North, Central and South America with all adjacent islands, Greenland, Bermuda, West Indies, Terra del Fuego, Galapagos, etc. Bulletin of the American Museum of Natural History, 29, 1 - 791. https: // doi. org / 10.5962 / bhl. title. 23819", "Brescovit, A. D. (1997) Revisao de Anyphaeninae Bertkau a nivel de generos na regiao Neotropical (Araneae, Anyphaenidae). Revista Brasileira de Zoologia, 13, 1 - 187. https: // doi. org / 10.1590 / S 0101 - 81751996000500001"]}